In vitro regeneration of Drosera burmannii Vahl.: a carnivorous plant of north-east India - Yanthan, J. Sureni (3 Biotech, 2017)
An efficient in vitro regeneration protocol has been developed from shoot tips of Drosera burmannii Vahl., a carnivorous plant of north-east India. Various plant growth regulators were used to study their efficacy in the induction of multiple shoots and roots. Of the various treatments, the maximum number of shoots (28.8 ± 1.5) and roots (9.7 ± 0.6) was observed in one-fourth strength standard medium (MS with 50 mg/l citric acid and 10 mg/l ascorbic acid) supplemented with 4 mg/l 6-benzylaminopurine (BAP) and 4 mg/l α-naphthalene acetic acid (NAA) followed by 26.8 ± 1.4 shoots in one-fourth strength SM fortified with 4 mg/l kinetin (KN) and 4 mg/l NAA. The well-developed plantlets with shoots and roots were potted in small plastic glasses filled with a mixture of sand and farmyard manure (3:1); these plantlets when transferred to a glasshouse for hardening and acclimatization showed 90% survival.